2018
DOI: 10.1038/s41598-018-32807-2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental simulations of volcanic ash resuspension by wind under the effects of atmospheric humidity

Abstract: Ash deposited during volcanic eruptions can be resuspended by wind and become hazardous for health and infrastructure hours to decades after an eruption. Accurate resuspension forecasting requires accurate modelling of the threshold friction velocity of the volcanic particles (Uth*), which is the key parameter controlling volcanic ash detachment by wind. Using an environmental wind tunnel facility this study provides much needed experimental data on volcanic particle resuspension, with the first systematic par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Regarding moisture content, material from Iceland can be suspended under moister atmospheric conditions (>70% relative humidity) than what is measured in other major dust sources of the world (for example those reported in Csavina et al (2014)). This finding coincides with laboratory studies done with volcanic ash from Eyjafjallajökull where suspension of grains was able to occur at all humidity levels (Del Bello et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Regarding moisture content, material from Iceland can be suspended under moister atmospheric conditions (>70% relative humidity) than what is measured in other major dust sources of the world (for example those reported in Csavina et al (2014)). This finding coincides with laboratory studies done with volcanic ash from Eyjafjallajökull where suspension of grains was able to occur at all humidity levels (Del Bello et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Del Bello et al () reported on a series of laboratory‐based measurements of u *t for ash samples from the Campi Flegrei region of Italy and Eyjafjallajökull in Iceland. They found that u *t was sensitive to RH, especially when RH was higher than 90% and when the particles considered were smaller than 63 μm (obtained by sieving).…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of traditional dust emission schemes to ash resuspension should be further investigated. In particular, future studies should aim at developing and validating specific emission schemes for volcanic ash based on recent experimental studies for ash resuspension [24,25]. In this work, emission flux was computed using a semi-empirical dust emission scheme based on the parameterisation proposed by Shao et al [51,52].…”
Section: Emission Schemementioning
confidence: 99%
“…Similarly, wind tunnel experiments carried out by Fowler and Lopushinsky [23] showed that freshly deposited ash can be resuspended at relatively low wind speeds, while consolidation of tephra-fallout deposits resulting from successive cycles of wetting and drying processes, caused a significant increase in the threshold wind velocity of erosion (i.e., the minimum wind speed required to mobilise the soil particles) [9]. More recently, Del Bello et al [24] conducted wind tunnel experiments under controlled ambient humidity conditions, highlighting that resuspension of smaller particles is hindered at high humidity levels. In parallel, Etyemezian et al [25] measured also emission rates and erosion thresholds in a humidity-controlled chamber using a small wind tunnel-like device.…”
Section: Introductionmentioning
confidence: 99%